Fitotoxidade de pyroxsulam com e sem óleo mineral em seis cultivares de trigo (triticum aestivum) - Jahn, Diandra Masurana (2018)
Wheat is a grass of great importance for the world production, existing several cultivars in the market. The objective of this work was to a alyze the phytotoxicity of the active ingredient Pyroxsulam for the wheat crop, when applied alone or with mineral oil addition. The experiment was carried out in the experimental area of the Universidade Tecnológica Federal do Paraná, Câmpus Dois Vizinhos. The design was completely randomized with four replications. For the experiment ten-liter vessels filled with local soil were used. Fifteen seeds were sown in each vase, and five plants per pot were left after germination and thinning. The treatments consisted of six wheat cultivars and the application of Pyroxsulam with or without mineral oil. Phytotoxicity, stem diameter, stature, tillering, number of leaves, root dry mass, aerial dry mass and aerial green mass were evaluated. These evaluations were carried out every seven days up to 52 days after sowing the wheat in the pots. It was concluded with this experiment that for all the evaluated cultivars there was no presence of phytotoxicity 21 days after the application of the treatments.